The dynamic external restriction to Mexico's growth through trade propensities, 1970-1999. - Loría Díaz, Eduardo (Estudios Económicos de El Colegio de México, 2001)
The Post Keynesian argument that the main limitation to growth -basically of any middle income country- is due to the trade deficit. This feature, which is structural, is called -within this frame work- External Constraint to Growth, ECG, through cointegration and ECM analysis for exports and imports functions, it is empirically demonstrated the dynamic evolution of the ECG, for 1970-1999. Despite the Mexican Economy is considerably linked to the international economy, manufacturing leads the growth process and several structural reforms have been implemented since 1985, the main conclusion is that the ECG has not changed.